Oh I've managed to figure it out!
Correct me if I'm wrong :
from (1) - y = 3 - kx
therefore x^2 + (3-kx)^2 = 5
x^2 + 9 - 6kx + 9 = 5
(k^2 + 1)x^2 - 6kx + 4 = 0
using b2 - 4ac to find real roots
(-6k)^2 - 16k^2 - 16 > 0
36k^2 - 16k^2 - 16 > 0
20k^2 > 16
k^2 > 4/5
-2/(5^(1/2)) < k > 2/(5^(1/2))
Hmm.. what program do people use to write proper it in proper mathematical form to post on these forums? That'd be helpful for the future.
Kermola
Ha-ha, I was early by 5 seconds!
The last line is incorrect.
See the LaTeX Help subforum. Wrap LaTeX code in [TEX]...[/TEX] tags.